2015
DOI: 10.14710/ijred.4.2.131-136
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Biodiesels from Calabash and Rubber Seeds Oils

Abstract: Physicochemical properties of biodiesel from vegetable oils depend on the inherent properties of the oil-producing seeds. The purpose of this study is to investigate the physicochemical properties of biodiesels extracted from calabash and rubber seeds oils, as well as their combined oil mixtures with a view to ascertaining the most suitable for biodiesel production. Calabash and rubber seeds oils were separately extracted through the use of a mechanical press with periodic addition of water. Biodiesels were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
2
1
0
Order By: Relevance
“…The cloud point of a bio-oil is the temperature below which the oil forms a cloudy appearance. The values cloud point of RSO from different regions was consistent with earlier reported literature [ 50 ]. Although, according to ASTM standard D 6751, no limit is specified for cloud point.…”
Section: Resultssupporting
confidence: 91%
“…The cloud point of a bio-oil is the temperature below which the oil forms a cloudy appearance. The values cloud point of RSO from different regions was consistent with earlier reported literature [ 50 ]. Although, according to ASTM standard D 6751, no limit is specified for cloud point.…”
Section: Resultssupporting
confidence: 91%
“…The linoleic acid classified as unsaturated fatty acids with the atomic number 18 and two double bonds. The same result reported Pianthong & Prachasanti (2009); Yousif et al (2013), Gimbun et al (2013), Bello & Otu (2015) and Awulu et al (2015) that the main content of rubber seed oil is linoleic acid with percentage of 41.38, 36.31, 20.07, 37.7 and 37.5 %, respectively. The results showed that the fatty acids from local and superior rubber seeds in Lahat district with altitude more than 600 m have a different composition than others.…”
Section: Characteristic Of Rubber Seed Oilsupporting
confidence: 79%
“…Second generation biodiesel is an alternative fuel that has the potential to replace fossil fuels [1][2][3]. Biodiesel is a mixture of methyl esters with long chain fatty acids made from non-toxic biological raw materials such as vegetable oils and animal oils [4,5]. Biodiesel as an alternative fuel for diesel engines offers several advantages, including its properties being almost the same as diesel fuel and can be used directly in diesel engines [6].…”
Section: Introductionmentioning
confidence: 99%